Effects of Equal Volume Heavy-Resistance Strength Training Versus Strength Endurance Training on Physical Fitness and Sport-Specific Performance in Young Elite Female Rowers - Thiele, Dirk; Prieske, Olaf; Lesinski, Melanie; Granacher, Urs (Frontiers in Physiology, 2020)
Strength training is an important means for performance development in young rowers. The most effective type of training is unresolved. The purpose of this study was to examine the effects of a 9-week equal volume heavy-resistance strength training (HRST) versus strength-endurance training (SET) in addition to regular rowing training on primary (e.g., maximal strength/power) and secondary outcomes (e.g., balance) in young rowers. Twenty-six female elite adolescent rowers were assigned to an HRST (n=12; age: 13.2±0.6 yrs; maturity-offset: +2.0±0.5 yrs) or a SET group (n=14; age: 13.1±0.5 yrs; maturity-offset: +2.1±0.5 yrs). HRST and SET comprised lower- (i.e., leg press/knee flexion/extension), upper-limbs (i.e., bench press/pull; lat-pull down), and complex exercises (i.e., rowing ergometer). HRST performed 4 sets with 12 repetitions per set at an intensity of 75-95% of the one-repetition maximum (1-RM). SET conducted 4 sets with 30 repetitions per set at 50-60% of the 1-RM. Training volume was matched for overall repetitions x intensity x training per week. Pre-post training, tests were performed for the assessment of primary (i.e., maximal strength [e.g., bench pull/knee flexion/extension 1-RM / isometric handgrip test], muscle power [e.g., medicine-ball push test, triple hop, drop jump, countermovement jump], cardiorespiratory endurance [CRE] [400-m run], sport-specific performance [700-m rowing ergometer trial]) and secondary outcomes (dynamic balance [Y-balance test], change-of-direction [CoD] speed [multistage shuttle-run test]). Adherence rate was >87% and one athlete of each group dropped out due to personal reasons. Overall, 24 athletes completed the study and no test or training-related injuries occurred. Significant group×time interactions were observed for maximal strength, muscle power, CRE, and CoD speed (p≤0.05; 0.35≤d≤1.45). Post-hoc analyses indicated larger gains in maximal strength and muscle power following HRST (p≤0.05; 1.81≤d≤3.58) compared with SET (p≤0.05; 1.04≤d≤2.30). Only HRST produced significant pre-post improvements for CRE and CoD speed (p≤0.05; 1.84≤d≤4.76). Further, results revealed significant main effects of time for sport-specific performance (p≤0.001; d=1.64). In conclusion, HRST in addition to regular rowing training was more effective than SET to improve selected measures of physical fitness (i.e., maximal strength, muscle power, CRE, CoD speed) in female elite young rowers. Training and/or growth/maturation could have induced sport-specific performance gains.